Analysis Study of Physics Digital Teaching Materials in Improving Critical Thinking Skills Student Participants: Literature Review - Suriza Putri; Festiyed; Fatni Mufit; Fuja Novitra (Postgraduate, University of Mataram, 2026)
In the context of physics learning, critical thinking is a key tool for students to understand complex and abstract natural phenomena. Physics requires students to possess strong analytical skills, logical problem-solving skills, and the ability to connect theory to reality. At present, technological developments demand teaching materials that are able to support physics learning to be more varied, interesting, and effective in honing students critical thinking. However, the use of digital teaching materials for this purpose has not been widely applied in schols, especially at the junior and widely known. This study aims to examine and review various national and international articles that develop or use digital teaching materials in physics learing. This research uses a qualitative method with a literature review approach. Data were collected from relevant articles and journals from 2018 to 2024. A total of 48 articles were identifies and analyzed using coding techniques to understand trens in digital teaching materials in improving critical thingking skills. The results showed that e-modules are the most widely developed and used digital teaching materials in research. This finding contributes that e-modulea can be a solution to improve students critical thinking skills through more innovative physics learning